Detection of BCR-ABL kinase domain mutations in patients with chronic myeloid leukemia on imatinib. (1st November 2013) - Chahardouli, Bahram; Zaker, Farhad; Mousavi, Seied Asadollah; Saffari, Zeinab; Nadali, Fatemeh; Ostadali, Mohammadreza; Ghadimi, Habibeh; Alimoghaddam, Kamran; Ghavamzade, Ardeshir; Rostami, Shahrbano
<x xml:space="preserve">Abstract</x> BCR-ABL tyrosine kinase domain mutations are the most important factor contributing to imatinib-resistance in patients with chronic myeloid leukemia. We used a semi-nested reverse transcriptase-polymerase chain reaction followed by bidirectional sequencing to detect mutations in a cohort of 110 chronic myeloid leukemia patients. In total, 34 mutations in 19 distinct codons were identified in 32 patients, of which D276N and E279A were novel. The most commonly mutated region was drug-binding site (29%) followed by P-loop region (26%) and most patients bearing them were in accelerated phase and blastic phase. This report expands the spectrum of BCR-ABL mutations and stresses the use of mutation testing in imatinib-resistant patients for continuation of treatment procedure.